Effect of Applying the Outdoor Learning Process on Concept Understanding and Scientific Attitude - Istanti Yuli Astuti; Djukri Djukri (Universitas Negeri Yogyakarta, 2026)
This study aims to determine the effect of applying the Outdoor Learning Process on concept understanding and scientific attitude regarding the Spermatophyta sub-material in Grade X students. Learning using the Outdoor Learning Process method was conducted in the greenhouse and school garden. This research is a quasi-experiment using a non-equivalent control group pretest & posttest design. The population in this study included all Grade X students of SMA Negeri 1 Jetis. The research sample was determined using cluster random sampling techniques, with class X1 as the experimental class and class X2 as the control class, totaling 64 students. Data collection was carried out through testing techniques, observation, interviews, and documentation. Research instruments used pretest and posttest questions. The obtained data were analyzed descriptively and inferentially. Inferential analysis used: MANOVA (Multivariate Analysis of Variance) to determine the effect of the Outdoor Learning Process on students' concept understanding, and Gain Score calculation to determine the improvement in students' concept understanding. The results showed that: the application of the Outdoor Learning Process affects the concept understanding of Spermatophyta sub-material in Grade X students, evidenced by a significance value of 0.000 < 0.05 and a medium improvement category from the N-Gain Score calculation of 0.7513. The Outdoor Learning method is able to accommodate students in obtaining direct learning experiences14. Direct learning experiences make students more enthusiastic about learning, more concentrated on the material, and develop their thinking power, thereby making it easier for students to understand the material better.